Eslabones y multiplicadores de la economía peruana - Torres Z., Jorge A. (1998)
This article presents an application of the input-output model to estimate linkages, among productive sectors, and multipliers of investment, employment and externa/ sector in the Peruvian economy. The objective is to derive a group of multipliers and ratios that allow a better knowledge of the relative importance of the economic sectors and summarize the characteristics of the Peruvían productive structure, which are difficult to visualize in aggregate form. The conclusion is that there exists a significative difference among the demand-induced impacts in the different sectors. The corolary is the need to use sectorial schemes, such as input-output models, to analyze economic impacts.